SOSIALISASI FLU BURUNG SERTA PEMERIKSAAN JUMLAH SEL DARAH PUTIH DAN TROMBOSIT PENDUDUK DESA BERABAN KABUPATEN TABANAN - LESTARI, A.A.WIRADEWI (Buletin Udayana Mengabdi, 2012)
ABSTRACT The counseling of Avian Influenza (AI) aimed to improve people knowledge about etiology, transmision, sign, symptom and prevention of AI. The improving people knowledge about AI was expected to change the people behavior, so this disease can be prevented. The measurement of white blood cell count and platelet count for people who is suffering from fever at Beraban Village in Tabanan Regency aimed to make AI early detection. The counseling of AI and early detection was done on Saturday, September 20th 2008 from 09.30 a.m. until finish, at SMP 3 Beraban. The counseling had been given by dr. A.A.Wiradewi Lestari, SpPK to 85 SMP 3 Beraban students. Free of charge measurement consisted of white blood cell count and platelet count for 10 people who is suffering from fever on September 19th 2008 until September 20th 2008. From ten people bing checked, no one has decreased of white blood cell count and platelet count